The spatiality of neighbourhood crime and the role of urban planning : the case of Mitchells Plain, Cape Town - Jacobs, Nathaneal Sidney (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.